2016
DOI: 10.1039/c6cs00090h
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reactions confined within carbon nanotubes

Abstract: In this critical review, we survey the wide range of chemical reactions that have been confined within carbon nanotubes, particularly emphasising how the pairwise interactions between the catalysts, reactants, transition states and products of a particular molecular transformation with the host nanotube can be used to control the yields and distributions of products of chemical reactions. We demonstrate that nanoscale confinement within carbon nanotubes enables the control of catalyst activity, morphology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
164
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(164 citation statements)
references
References 139 publications
(324 reference statements)
0
164
0
Order By: Relevance
“…It is noted that NCs prepared by modifying CNT with FeS 2 particles have attracted a great deal of consideration as a catalytic material due to its chemical, structural, physical, and optical properties ,. The formation energy of oxygen vacancies and metal interstitials in FeS 2 NCs is very low and thus the defects are formed easily compared to other materials making the material suitable for catalyzing an electrochemical process . In the present study, FeS 2 ‐CNT NCs was synthesized and immobilized on a GCE to check the possibility of catalyzing the oxidation of 4‐AP molecules such that p‐quinone can be synthesized in the aqueous medium.…”
Section: Introductionmentioning
confidence: 96%
“…It is noted that NCs prepared by modifying CNT with FeS 2 particles have attracted a great deal of consideration as a catalytic material due to its chemical, structural, physical, and optical properties ,. The formation energy of oxygen vacancies and metal interstitials in FeS 2 NCs is very low and thus the defects are formed easily compared to other materials making the material suitable for catalyzing an electrochemical process . In the present study, FeS 2 ‐CNT NCs was synthesized and immobilized on a GCE to check the possibility of catalyzing the oxidation of 4‐AP molecules such that p‐quinone can be synthesized in the aqueous medium.…”
Section: Introductionmentioning
confidence: 96%
“…To solve this problem, confined synthesis method, as an extension of the template‐assisted synthesis method, has been proposed. Confinement, a concept coming from catalysis and surface science, has been utilized for the restriction of nanoparticles or molecules in a nanospace or on the surface to improve their catalytic properties 15–20. In the field of materials science and engineering, the concept of confinement has also been developed for the controlled synthesis of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical investigations reveal that the spatially confined environment increases the molecular orbital energy and changes activity of the confined molecules, which have been recognized as the nest effect and quantum confinement effect (15, 16). In past decades, some experimental studies have demonstrated that carbon nanotubes (CNTs) strongly affect catalytic reactions occurring inside the nanotubes (7,17,18), and confined catalysis in 1D nanocavities has been theoretically addressed by studying molecule adsorption on metal clusters encapsulated in CNTs (19). As illustrated in Fig.…”
mentioning
confidence: 99%